Treatment option for sepsis in children in the era of antibiotic resistance. Issue 10 (October 2014) - Lutsar, Irja; Telling, Kaidi; Metsvaht, Tuuli
Abstract : Sepsis caused by multidrug-resistant microorganisms is one of the most serious infectious diseases of childhood and poses significant challenges for pediatricians involved in management of critically ill children. This review discusses the use of pharmacokinetic/dynamic principles (i.e., prolonged infusion of β-lactams and vancomycin, once-daily administration of aminoglycosides and rationale of therapeutic drug monitoring) when prescribing antibiotics to critically ill patients. The potential of 'old' agents (i.e., colistin, fosfomycin) and newly approved antibiotics is critically reviewed. The pros and cons of combination antibacterial therapy are discussed and finally suggestions for the treatment of sepsis caused by multidrug-resistant organisms are provided.